2005
DOI: 10.1126/science.1103096
|View full text |Cite
|
Sign up to set email alerts
|

Large Sulfur Bacteria and the Formation of Phosphorite

Abstract: Phosphorite deposits in marine sediments are a long-term sink for an essential nutrient, phosphorus. Here we show that apatite abundance in sediments on the Namibian shelf correlates with the abundance and activity of the giant sulfur bacterium Thiomargarita namibiensis, which suggests that sulfur bacteria drive phosphogenesis. Sediments populated by Thiomargarita showed sharp peaks of pore water phosphate (/=50 grams of phosphorus per kilogram). Labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
375
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 384 publications
(397 citation statements)
references
References 13 publications
12
375
0
1
Order By: Relevance
“…These include nitrate and sulphur accumulation, mixotrophic assimilation of CO 2 and organic substrates such as acetate, and the ability to perform dissimilatory nitrate reduction to ammonium (DNRA; Fossing et al, 1995;McHatton et al, 1996;Otte et al, 1999;Schulz et al,1999;Sayama et al, 2005). Recent genomic studies of Beggiatoa and physiological studies of Thiomargarita (Schulz and de Beer 2002;Schulz and Schulz 2005;Mussman et al, 2007) indicate that the giant sulphur bacteria have diverse pathways of energy metabolism, which includes both DNRA and denitrification, oxygen respiration and an auxiliary energy reservoir of polyphosphate. The question arises whether these properties also apply to Thioploca.…”
Section: Introductionmentioning
confidence: 99%
“…These include nitrate and sulphur accumulation, mixotrophic assimilation of CO 2 and organic substrates such as acetate, and the ability to perform dissimilatory nitrate reduction to ammonium (DNRA; Fossing et al, 1995;McHatton et al, 1996;Otte et al, 1999;Schulz et al,1999;Sayama et al, 2005). Recent genomic studies of Beggiatoa and physiological studies of Thiomargarita (Schulz and de Beer 2002;Schulz and Schulz 2005;Mussman et al, 2007) indicate that the giant sulphur bacteria have diverse pathways of energy metabolism, which includes both DNRA and denitrification, oxygen respiration and an auxiliary energy reservoir of polyphosphate. The question arises whether these properties also apply to Thioploca.…”
Section: Introductionmentioning
confidence: 99%
“…For intracellular polyphosphate staining, intact Thioploca filaments were immersed in toluidine blue solution as described previously [39]. To detect glycogen and other polyglucose storage molecules, Lugol staining was also carried out [39].…”
Section: Characterization Of Thioploca and Its Habitat In Lake Okotanpementioning
confidence: 99%
“…They can accumulate large amounts of nitrate and elemental sulfur, and use them for respiration. In addition to the elements mentioned above, nitrate-storing sulfur oxidizers may influence the phosphorus cycle, as it has been shown that some of them accumulate phosphorus as polyphosphate in their cells [4,39]. The intracellular accumulation of polyphosphate to overcome physical and chemical stress is widespread among microorganisms [5,12,23,28], although absence of polyphosphate granules in cells of Thioploca has been repeatedly reported [14,15,16,22].…”
Section: Introductionmentioning
confidence: 99%
“…Arning et al, 2009) in continental shelf environments where upwelling of nutrient-rich, deep-ocean water facilitates high biological production (Föllmi, 1996). Fluctuating anoxic-suboxic redox conditions and redox-dependent microbial processes within the sediment pore space leads to elevated phosphate concentrations resulting in apatite precipitation (Schulz and Schulz, 2005).…”
Section: Environmental Interpretationmentioning
confidence: 99%
“…Fe/Mn redox cycling and mineralization of organic matter by bacterial sulfate reduction and/or emergence of habitats for sulfur-bacteria (Krajewski et al, 1994, Schulz and Schulz, 2005, Nelson et al, 2010and Lepland et al, 2014, the phosphate concentration and precipitation during the Paleoproterozoic would have required establishment of suboxic or oxic seawater conditions and, most importantly, development of fluctuating redox conditions in sediments that is crucial for concentrating interstitial phosphate.…”
Section: Introductionmentioning
confidence: 99%